Computations of mixed convection slip flow around the surface of a sphere: Effects of thermophoretic transportation and viscous dissipation - Ashraf, Muhammad; Abbas, Amir; Öztop, Hakan Fehmi; Nisar, Kottakkaran S.; Khan, Ilyas (Wiley, 2021)
The effects of thermophoretic motion and viscous dissipation on the two-dimensional fluid flowing along different positions of a sphere are inspected by considering slip flow. The leading set of partial differential equations is altered as a set of nonlinear primitive partial differential equations utilizing primitive variable transformation. The finite difference method is used to solve the governing equations numerically. The impacts of appropriate parameters, such as Eckert number slip flow parameters, mixed convection parameter, and thermophoresis parameter on unknown variables, such as velocity profile, mass concentration, and temperature profile are analyzed and displayed with the help of graphs by using the highly technical software, Tecplot 360. And also, we have observed the effects of the identical parameters on skin friction coefficient, rate of heat, and rate of mass transfers by means of graphs. From the outcomes, we noted that (a) the velocity profile is dominant at position X = 1.5 rad and the temperature distribution and mass concentration are dominant at position X = pi rad for increasing values of Eckert number. (b) Slip parameter boosts the velocity at position X = 2.095 rad but temperature and mass concentration are maximum at position X = pi rad. (c) The thermophoretic parameter is also having a very strong impact on heat and fluid flow mechanics. The slip flow provides benefits in improving heat and mass transfer mechanisms along with skin friction. It is also predicted that the concentration boundary layer will be thinner during thermophoresis around the different positions. The novelty of the predicted work is holding slip flow with the inclusion of mechanical energy and thermophoretic motion around different positions of the sphere. It is worth mentioning that the obtained results predicted in graphs are satisfied by the prescribed boundary conditions, which yield the corrected skin friction, rate of heat transfer, and rate of mass transfer.
Keywords: mixed convection; slip flow; sphere; thermophoretic transportation; viscous dissipation